The evaluation of the reactivating and therapeutic efficacy of three novel bispyridinium oximes (K454, K456, K458) in comparison with the oxime K203 and trimedoxime in tabun-poisoned rats and mice. (February 2013) - Kassa, Jiri; Sepsova, Vendula; Musilek, Kamil; Horova, Anna
<x xml:space="preserve">Abstract</x> The potency of three newly developed bispyridinium compounds (K454, K456, K458) to reactivate tabun-inhibited acetylcholinesterase and reduce tabun-induced lethal toxic effects was compared with the oxime K203 and trimedoxime using in vivo methods. The study determining percentage of reactivation of tabun-inhibited diaphragm and brain acetylcholinesterase in poisoned rats showed that the reactivating efficacy of all newly developed oximes is comparable with K203 but lower than the reactivating potency of trimedoxime in diaphragm. In the brain, their potency to reactivate tabun-inhibited acetylcholinesterase is lower compared with trimedoxime and the oxime K203. All three newly developed oximes were also found to be relatively effective in reducing lethal toxic effects in tabun-poisoned mice. Their therapeutic efficacy is consistent with the therapeutic potency of the oxime K203. On the other hand, their potency to reduce acute toxicity of tabun is significantly lower compared with trimedoxime. In conclusion, the reactivating and therapeutic potency of all three newly developed oximes does not prevail the effectiveness of the oxime K203 and trimedoxime and, therefore, they are not suitable for their replacement of commonly used oximes for the treatment of acute tabun poisoning.